THE DEVELOPMENT OF FLASHCARD MEDIA TO IMPROVE BILINGUAL ABILITY IN THE KINDERGARTEN - Ety Youhanita; Durrotun Nafisah; Evi Aulia Rachma; Ratna Nurdiana; Nur Fithria Wiji Astutik (JURNAL PAJAR (Pendidikan dan Pengajaran), 2023)
Education is one of the important fields or elements in the progress of the State, therefore, the government is currently carrying out an educational revolution which aims to improve the quality of education in the terms of basic and high level learning. One of the efforts to improve the quality of education is by increasing bilingual ability in the kindergarten. Bilingual ability is the ability which use two languages as a means of daily communication, the bilingual ability can be developed through the bilingual learning which is taught early to the students which has the benefit to develops the students' cognitive abilities, and introduces the students to a more diverse foreign culture. To develop the bilingual ability at the basic level, flashcard media will be developed with the aim of improving the bilingual ability in the kindergarten in the group B at Cambodian Kindergarten in Lamongan with the theme of transportation that meets the validity criteria and practicality criteria for the kindergarten students. The test result of the flashcard media of the material experts was 89.9% with very good criteria and the test result of the media experts was 76.8% with good criteria. While the test result of the individual was 91.2% with very good criteria, the test result of the small group was 90.6% with very good criteria and the test result of large group was 92.2% with very good criteria. From the test results, it shows that the development of the flashcard media is suitable with the learning objectives set and the use of flashcard media can achieve the learning objectives to improve the bilingual ability in the kindergarten.